Effects of 2, 4‐dichlorophenoxyacetic acid on the expression of NLRP3 inflammasome and autophagy‐related proteins as well as the protective effect of Lycium barbarum polysaccharide in neonatal rats. Issue 12 (31st August 2021) - Zhou, Jian; Li, Honghui; Wang, Faxuan; Wang, Hengquan; Chai, Ru; Li, Jiangping; Jia, Leina; Wang, Kai; Zhang, Pengju; Zhu, Lingqin; Yang, Huifang
Abstract: The pesticide 2, 4‐dichlorophenoxyacetic acid (2, 4‐D) has neurotoxic effects, but its mechanism is not clear. In this study, a 2, 4‐D (75 mg/kg. b.w) exposure model was established in SD rats with colostrum. Lipopolysaccharide (1 mg/kg b.w) was used as the positive control, and Lycium barbarum polysaccharide (LBP, 50 mg/kg b.w) was used as an intervention factor to explore the neurotoxic effect of 2, 4‐D and the neuroprotective effect of LBP. Our research results show that 2, 4‐D causes a decrease in the number of hippocampal CA3 pyramidal cells and pyknosis in nuclei with a triangular or irregular shape and that rats show signs of anxiety or depression. In rat serum, superoxide dismutase, and glutathione peroxidase activity decreased, while malondialdehyde content increased. Protein and mRNA levels of TNFα, IL‐6, IL‐1β, IL‐18, NLRP3, ASC, caspase‐1, IL‐1β, IL‐18, and p62 increased, while those of LC3‐II/LC3‐I and Beclin‐1 decreased in hippocampal tissues. In conclusion, 2, 4‐D increased the oxidative stress level, induced neuroinflammatory response, and decreased the autophagy level in experimental rats. LBP may have upregulated the autophagy level in the body by inhibiting the activation of the NLRP3 inflammasome, thus playing a neuroprotective role.